Vacant urban areas: Causes and interconnected factors. (February 2018) - Newman, Galen; Park, Yunmi; Bowman, Ann O'.M.; Lee, Ryun Jung
Abstract: Vacant urban areas (VUAs) can consist of both vacant land and abandoned structures. In this article, the authors summarize a recent survey on VUA, examine current conditions and causes of VUA, and explore the possible interconnections among these conditions and causes. The research examines employment, fiscal position, elasticity, population alteration, and regional location as primary variables. We find that VUAs are not interchangeable indicators of urban decay. Vacant land is most often associated with cities that have expanded their political boundaries while structural abandonment is more related to a city's population loss. Improvement of the local economy may not necessarily help reduce vacant land while structural abandonment is more sensitive to a city's economic status. Regional planning for VUAs, the strategic location of new industries and jobs, and new population/density regulatory approaches could be the next phase in addressing VUA changes. Highlights: Increases and decreases in VUAs can help determine a city's future. A city has 16.7% vacant land and 23.5 vacant addresses per 1000 people, on average. Research focuses on local-scaled approaches to reuse VUAs rather than its causes. Vacant land is linked to urban expansion; abandonment is linked to depopulation. Regional based planning strategies for VUAs are the next phase in management.